Gender aspects in chronic myeloid leukemia: long-term results from randomized studies - Berger, Ute; Maywald, Ole; Pfirrmann, M.; Lahaye, T.; Hochhaus, Andreas; Reiter, Andreas; Hasford, J.; Heimpel, H.; Hossfeld, D. K.; Kolb, H.-J.; Löffler, H.; Pralle, H.; et al. (Leukemia, 2005)
Gender-related aspects in chronic myeloid leukemia (CML) have not been studied well. We therefore analyzed 856 patients with Ph/BCR-ABL-positive CML from the German randomized CML-studies I (interferon α (IFN) vs hydroxyurea (HU) vs busulfan) and II (IFN+HU vs HU alone). The median observation time was 8.6 years. A total of 503 patients (59%) were male. Female patients were older (51 vs 46 years; P<0.0001), presented with lower hemoglobin (11.7 vs 12.5 g/dl; P<0.0001), higher platelet counts (459 vs 355 × 109/l; P<0.0001), smaller spleen size (3 vs 4 cm below costal margin; P=0.0097), a lower rate of additional cytogenetic aberrations (9 vs 15%; P=0.018) and a less favorable risk profile (P=0.036). The transplantation rate was 14% for female (n=48) and 22% for male patients (n=113). Median survival was longer in female patients (58 vs 49 months; P=0.035) mainly attributable to better survival in the low- and intermediate-risk groups and, independent from risk groups, in the HU group. These results were confirmed by matched-pair analyses based on German population data (n=496, 59 vs 45 months; P=0.0006). This is the first analysis of gender aspects in CML using randomized trials. It demonstrates the relevance of analyses of gender differences in CML and in malignant disease at large.